CASHLESS PAYMENTS (Innovative Technologica: Methodical Research Journal, 2023)
This article describes in detail the system of cashless settlements and their elements, the implementation and improvement of cashless settlements, the features of the use of monetary forms in monetary relations that occur in the economy, and the first principle of cashless settlements today.